SELECTED RESULTS OBTAINED AT SYOWA STATION, ANTARCTICA, BY RECEPTION OF KYOKKO AND ISIS SATELLITE DATA - ナガタ, タケシ; ヒラサワ, タケオ; フクニシ, ヒロシ; サトウ, ナツオ; ヨシノ, タケオ; NAGATA, Takesi; HIRASAWA, Takeo; FUKUNISHI, Hiroshi; SATO, Natsuo; YOSHINO, Takeo (1980)
P(論文) Satellite data acquisition facilities for ISIS-1 and -2 and EXOS-A (Kyokko) were installed at Syowa Station in January 1976. The VLF wideband and topside sounder data measured on ISIS-1 and -2 have been received on the routine basis since April 1976. The total number of the ISIS-1 and -2 passes received at Syowa Station in the period from April 1976 to August 1979 are 476 and 654,respectively. The reception of telemetry signals from EXOS-A began in February 1978. The total number of the passes received in the period of February 1978-August 1979 is 427. From the VLF wideband data measured with these satellites, emission regions of VLF hiss and saucer have been investigated. It is found that the hiss emission region with occurrence probability larger than 50% is located at 75°-85°geomagnetic latitude between 10h and 14h MLT on the dayside, and at 65°-80°geomagnetic latitude between 20h and 02h MLT on the nightside, while the saucer emission region with occurrence probability larger than 30% is located at 75°-85°between 10h and 18h MLT on the dayside and at 60°-70°between 18 and 02h MLT on the nightside. It is suggested that the hiss and saucer emission regions are closely associated with field-aligned currents. departmental bulletin paper